Strategi Branding dan Promosi dalam Menarik Jamaah Umroh di PT Dzaki Anugerah Wisata Palembang - Abdillah Destariansyah; Hasril Atieq Pohan; Bela Janare Putra (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to identify the branding and promotional strategies implemented by PT Dzaki Anugerah Wisata Palembang in attracting prospective Umrah pilgrims, as well as to examine the supporting and inhibiting factors in their implementation. This research employs a qualitative method with a descriptive approach. Data collection techniques include interviews, observations, and documentation. The results indicate that the branding strategy applied by PT Dzaki Anugerah Wisata Palembang is carried out through the development of a consistent brand identity, professional services, and the establishment of trust among pilgrims through safe and comfortable worship experiences. The utilization of social media platforms such as Instagram and WhatsApp, as well as recommendations from previous pilgrims (word of mouth), also strengthens the company’s brand awareness and image. Meanwhile, the promotional strategy is implemented through the use of a promotional mix, including digital advertising, sales promotions such as discounts and flexible payment options, personal selling through direct communication with prospective pilgrims, and public relations activities such as religious gatherings and collaborations with religious leaders. These strategies have been effective in increasing public interest and trust in the Umrah services offered. However, the company still faces several challenges, such as competition among Umrah travel agencies and the inability to fully achieve the targeted number of pilgrims.